Estresse, cortisol e dor musculoesquelética em enfermeiros de um serviço de hemato-oncologia - Guerreiro, Monique Pereira Portella (2019)
Introduction: Occupational stress is understood as the result of the interaction between the demands of work and the ability to control them, which can lead to changes in cortisol concentration. It exposes the worker to the risk of becoming ill, and to the development of musculoskeletal pain. Objective: to evaluate the association between occupational stress, salivary cortisol concentration and musculoskeletal pain in nurses at a Hemato-Oncology service. Method: A cross-sectional study was carried out with 29 day-care nurses from a Hemato-Oncology service at a university hospital in Rio Grande do Sul. Data were collected from April to August, 2018, with a sociodemographic, occupational and profile characterization tool the Job Stress Scale, the Nordic Osteomuscular Symptoms Questionnaire, and saliva collection for cortisol analysis in five moments (upon waking, at the beginning and end of shift on a work day and at the same time on a day off ). Data were analyzed statistically. Results: Two articles were constructed. The first one entitled "Salivary cortisol stress evaluation in hemato-oncology nurses: work x gap", showed that there was no significant difference (p <0.05) in salivary cortisol values between the workday and the day off duty. There was a significant difference with the highest values of salivary cortisol on awakening for those who do not have children, do not use medication, do not use oral contraceptives and intend to leave work. At the beginning of the day, for those who use medication. And, at the end of the holiday for those who work in the hospitalization sector. The second article, entitled "Occupational stress, cortisol concentration and musculoskeletal pain: what is its association in hemato-oncology nurses?", showed that the greatest number of nurses were in the passive work and high demand quadrants, which were also the quadrants with the highest prevalence of musculoskeletal pain. The anatomical regions with the highest reported musculoskeletal pain were vertebral column in the last year and lower limbs in the last week, and the pain intensity was moderate to mild. There was no significant difference between salivary cortisol values with occupational stress and with musculoskeletal pain. Conclusion: the data show that hemato-oncology nurses are stressed and possibly have developed an occupational disease, which was noticed from reports of musculoskeletal pain, and manifestations of changes in the physiological parameters of salivary cortisol. Interventions are suggested in order to prevent the worsening of the psychological and physical conditions, in order to maintain the quality of service and health of the professionals.